Ink‐Jet Printed CMOS Electronics from Oxide Semiconductors. Issue 29 (13th April 2015) - Garlapati, Suresh Kumar; Baby, Tessy Theres; Dehm, Simone; Hammad, Mohammed; Chakravadhanula, Venkata Sai Kiran; Kruk, Robert; Hahn, Horst; Dasgupta, Subho
<x xml:space="preserve">Abstract</x> Complementary metal oxide semiconductor (CMOS) technology with high transconductance and signal gain is mandatory for practicable digital/analog logic electronics. However, high performance all‐oxide CMOS logics are scarcely reported in the literature; specifically, not at all for solution‐processed/printed transistors. As a major step toward solution‐processed all‐oxide electronics, here it is shown that using a highly efficient electrolyte‐gating approach one can obtain printed and low‐voltage operated oxide CMOS logics with high signal gain (≈21 at a supply voltage of only 1.5 V) and low static power dissipation.